IMPLEMENTATION OF INNOVATIVE HUMAN RESOURCE MANAGEMENT STRATEGIES IN THE ERA OF DIGITAL TRANSFORMATION - Eloh Bahiroh; Sri Ndaru Arthawati (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2026)
This article analyses the implementation of innovative human resource management (HRM) strategies in the era of digital transformation through a literature review. It focuses on two main discussions: (1) strategies such as HRIS, AI recruitment, agile HR, talent analytics, e-learning, digital onboarding, digital OKRs, and hybrid work that increase efficiency by 30–60%, talent retention by 25–35%, and productivity by 40%; (2) challenges such as employee resistance of 65%, a digital skills gap of 35–40%, data breach risks, AI bias, hybrid burnout of 25%, and holistic solutions via ADKAR change management, cloud SaaS, ethical AI frameworks, and open-source tools that achieve an 85% success rate in Indonesian organisations (BCA, Gojek, Tokopedia, Telkom).